Pengaruh Self Esteem, Self Efficacy, Dan Locus Of Control Terhadap Kinerja Pegawai Di Lpd Desa Adat Kerobokan - Ni Kadek Ayu Dwi Apriyanti; I Putu Bagus Suthanaya; Ni Luh Komang Julyanti Paramita Sari (Journal Research of Management, 2024)
Worker execution is the result accomplished by a individual concurring to appropriate guidelines inside a certain period of time so that representative execution can be made strides by representatives and carry out their obligations. Worker execution can be seen from the work comes about appeared by the worker. In an exertion to move forward representative execution, self-esteem, self-efficacy and locus of control are things that representatives must pay consideration to and execute. This inquire about points to decide the impact of self-esteem, self-efficacy and locus of control on representative execution at the Kerobokan Conventional Town Town Credit Institution (LPD). This investigate strategy utilized may be a quantitative strategy. The number of tests utilized was 70 representatives. The testing procedure utilized was soaked examining. The conclusion gotten is that self-esteem encompasses a positive effect on representative execution. Self-efficacy incorporates a positive impact on worker execution. Locus of control features a positive impact on representative execution. This implies that the way better self-esteem, self-efficacy and locus of control will be able to move forward representative execution.